PELATIHAN DAN EDUKASI PEMBERIAN MAKANAN PENDAMPING ASI (MP ASI ) PADA IBU BALITA - Eka Oktavianto Oktavianto (ABDIMAS Madani, 2021)
Abstract Starting at the right time, solid complementary feeding will be very beneficial for meeting the nutritional needs and growth of the baby. Inappropriate complementary feeding of breastfeeding is one of the causes of malnutrition in toddlers. The purpose of this community service activity is to improve the knowledge and abilities of mothers in giving complementary breastfeeding. The target of this activity is mothers in the Posyandu Harapan Dusun Trukan Pleret who have toddlers. The activity method is to conduct lectures, simulation and supervision. The lecture was held for 1 hour and 30 minutes using power point media, after which a practice or simulation of making complementary feeding schedules was carried out. After that, supervision is carried out to help mothers when practicing it at home. When giving the material, the participants focused on paying attention and some of them asked questions and conveyed their experiences in giving complementary foods to their babies. There was an increase in the score of knowledge and skills related to complementary feeding. The conclusion is that this community service activity is effective in increasing the understanding and ability of mothers to provide complementary foods.